International Physical Activity Questionnaire: validation and assessment in an Italian sample (Italian Journal of Public Health, 2010)
Background: A standardized method for the assessment of physical activity, the International PhysicalActivity Questionnaire (IPAQ), was developed in the late 1990s as instrument for cross-national assessment.This study aims to evaluate the reliability and validity of the IPAQ short and long version questionnaire in aItalian sample.Methods: The long and short versions of IPAQ questionnaires were administered twice, with an intervalof one day between each administration, to 2 different random samples. Cronbach’s alpha was used as ameasure of the internal consistency of the two versions.Results: The long version was administered to 60 subjects and the short version to 58. The Cronbach’s alphaon items about physical activity in the long version was 0.73, and 0.60 for the short version. The referredcomments on short and long version were not very different both in number and content though they suggesta better understanding of the short version compared to the long one.Discussion: IPAQ short and long versions show acceptable reliability properties in the Italian adult setting.The utilization of a questionnaire seems be more influenced by time of administration and number ofrequested information. In terms of internal consistency and validity they appear to have similar performance.
Keywords: IPAQ; physical activity; questionnaire; validation